Radical atheism and religious power: new atheist politics - McAnulla, Stuart (Approaching Religion, 2012)
The increased visibility of assertive forms of atheism has provoked much public debate. This article argues that new atheism primarily seeks to contest what it considers to be the unjustifiably powerful role of religion through a multifaceted challenge to religious beliefs, practices and institutions. Influential theories of power are drawn upon to unpack the character of new atheist positions. It is proposed that new atheism seeks to challenge four perceived ‘dimensions‘ of religious power, in particular (i) religion’s role in public decision-making; (ii) the ability of religious groups to shape policy agendas; (iii) the power of religion to create preferences that run counter to an individual’s true interests and, (iv) the role of religion in constituting forms of subjectivity more generally. Focussing particularly on the role of atheism in the UK, the paper also considers the implications such thinking has had on atheist practice and activism. The paper also considers how defenders of religion have reacted to the challenges posed by new atheism. It is argued that religious groups and authors have largely focussed on defending the role of religious faith and the significance of God in people’s lives, rather than explicitly defending what new atheists consider to be the unfair institutional privilege accorded to some religious organisations.